2013
DOI: 10.7763/ijet.2013.v5.600
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Agent-Based Human Behavior Simulation with Building Information Modeling for Building Design

Abstract: Abstract-Human behavior needs to be considered when designing buildings and infrastructures. In recent decades, building information modeling (BIM) has been increasingly adopted as a computer aided design methodology for architectural design, engineering design simulation and evaluation, and 4D constructability analysis. BIM models can be used to conduct engineering analyses while human behavior simulation using BIM models is still lacking. The research objective of this study is to connect BIM software with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…In fact, different methods can be integrated into an agentbased model. For example, Cheng and Gan (2013) analyzed evacuation time in different predefined scenarios integrating BIM with behavioral models. Similarly, Marzouk and Daour (2018) used BIM and ABM together for evacuation simulation of labors as an input for a Multi-Criteria Decision-Making process considering total project time, total cost, and evacuation time to achieve the optimum construction method scenario.…”
Section: Emergence and Complexity In Agent-based Modelingmentioning
confidence: 99%
“…In fact, different methods can be integrated into an agentbased model. For example, Cheng and Gan (2013) analyzed evacuation time in different predefined scenarios integrating BIM with behavioral models. Similarly, Marzouk and Daour (2018) used BIM and ABM together for evacuation simulation of labors as an input for a Multi-Criteria Decision-Making process considering total project time, total cost, and evacuation time to achieve the optimum construction method scenario.…”
Section: Emergence and Complexity In Agent-based Modelingmentioning
confidence: 99%
“…An influential point of departure for this research is BIM-based simulations for serious games to aid in fire safety management. Studies [31][32][33][34] that used BIM-based games as a research instrument to observe human behaviour demonstrated the fidelity of such simulations, particularly agent-based simulations. BIM, combined with other platforms such as GIS [33], can provide the data necessary for such accurate simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This, the authors of the specified work argue, defines prospects for projects' improvement. However, the model, proposed in [11], focuses only on the interests of the end-user of a building and does not include other basic aspects of project management.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Study [11] proposes to consider building information modeling (BIM) in a combination with behavior of the project stakeholders. This, the authors of the specified work argue, defines prospects for projects' improvement.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%